How effective are social distancing policies? Evidence on the fight against COVID-19 - Ulrich Glogowsky; Emanuel Hansen; Simeon Schächtele (Johannes Kepler University of Linz, Department of Economics, 2020)
To fight the spread of COVID-19, many countries implemented unprecedented social distancing policies. This is the first paper that uses an event-study approach to examine the effects of the German social distancing policies on (a) individual behavior and (b) the spread of the epidemic. Combining administrative health data and cell phone data, we find that the policies, first, heavily reduced citizens' mobility and, second, strongly contained the epidemic. In comparison to a benchmark without social distancing, within three weeks, the policies avoided 84% of the potential COVID-19 cases (point estimate: 499.3K) and 66% of the potential fatalities (5.4K).
Keywords: I18; H12; I12; 330; COVID-19; social distancing policies; policy evaluation; mobility behavior